2008
DOI: 10.1113/jphysiol.2007.142877
|View full text |Cite
|
Sign up to set email alerts
|

Apical SK potassium channels and Ca2+‐dependent anion secretion in endometrial epithelial cells

Abstract: Apical uridine triphosphate (UTP) stimulation was shown to increase short circuit current (I sc ) in immortalized porcine endometrial gland epithelial monolayers. Pretreatment with the bee venom toxin apamin enhanced this response. Voltage-clamp experiments using amphotericin B-permeablized monolayers revealed that the apamin-sensitive current increased immediately after UTP stimulation and was K + dependent. The current-voltage relationship was slightly inwardly rectifying with a reversal potential of −52 ± 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…1) indicating an absolute requirement for activation of a basolateral K ϩ channels to promote the transient secretory response observed. Luminal oviduct K ϩ is normally higher than plasma thus an active K ϩ secretory mechanism is likely to exist as has been shown in the uterus (34). Here we show that apical K ϩ channel inhibition reduced basal and ATP e -activated current most likely due to depolarization of the apical cell membrane resulting in a reduced driving force for anion secretion and thus reduced secretory current.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…1) indicating an absolute requirement for activation of a basolateral K ϩ channels to promote the transient secretory response observed. Luminal oviduct K ϩ is normally higher than plasma thus an active K ϩ secretory mechanism is likely to exist as has been shown in the uterus (34). Here we show that apical K ϩ channel inhibition reduced basal and ATP e -activated current most likely due to depolarization of the apical cell membrane resulting in a reduced driving force for anion secretion and thus reduced secretory current.…”
Section: Discussionsupporting
confidence: 67%
“…Over ten years ago the presence of a large conductance maxi-K ϩ channel type in the apical membranes of rabbit oviduct was reported (23). More recently the presence of calcium-activated potassium channels in the apical membrane of porcine endometrial epithelia, cells closely related to the oviduct, has been reported (34). In the majority of polarized epithelia, two principle types of basolateral K ϩ conductances have been described, activated by either an increase in cAMP or intracellular calcium providing an electrical driving force for chloride secretion (5,6,30).…”
mentioning
confidence: 99%
“…Apamin-sensitive SK channels are activated by 17β-estradiol (E2) in gonadotropin-releasing hormone (GnRH) neurons [9]. Estrogen elevates the SK3 mRNA expression in the rostral basal hypothalamus [10], endometrial epithelial cells [11], and myometrial cells [12]. Furthermore, the overexpression of SK3 channels dampens uterine contractility [13].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the immortalized porcine glandular endometrial epithelial cell culture (PEG) was characterized and represented as the normal cell culture for examining the effects of Ge and Di on the epithelial function (Palmer et al 2008, Deachapunya & Poonyachoti 2013. Thus, in this study, we aimed to investigate whether the soy isoflavones, Ge or Di, alter the endometrial barrier function in the PEG cells as determined by TER and FITC-dextran flux (FD-4).…”
Section: Introductionmentioning
confidence: 99%